Effectiveness Deep Breathing and Progressive Muscle Relaxation Training (PMRT) Techniques to Reduce Anxiety in Pregnant Woman Pre-Birth - Hayati, Sri Ayatina; Sutoyo, Anwar; Awalya, Awalya (Jurnal Bimbingan Konseling, 2018)
This study aims to examine the effectiveness of deep breathing and progressive muscle relaxation training (PMRT) techniques for pre-natal pregnant women's anxiety at Puskesmas 9 November Banjarmasin. The research method used repetead measure experiment design and the research design used was pretest and multiple posttest design. The research population is 99 and 36 samples are determined by using purposive sampling technique. Instruments used scale The Perinatal Anxiety Screening Scale (PASS). Data analysis technique used data analysis method: descriptive analysis, normality test, sphericity test, and parametric statistic with One Repeated Measure One-Way Analysis of Variance (ANOVA) test. The results showed deep breathing technique and progressive muscle relaxation training technique (PMRT) effective to reduce the anxiety of pregnant mother pre-delivery at Puskesmas 9 November Banjarmasin. Judging from the difference of effectiveness level, progressive muscle relaxation training (PMRT) technique is more effective than deep breathing technique. This study provides clarification of treatment of anxiety problems of pregnant women pre-delivery with deep breathing techniques and techniques progressive muscle relaxation training (PMRT).